Career guidance: an option in secondary education (CONOCIMIENTO, INVESTIGACIÓN Y EDUCACIÓN CIE, 2017)
It is a career guidance proposal for secondary school students as an option to contribute significantly to their life projects. Given the need, some guidelines were established.These guidelines serve to shape and strengthen values, as an integral part of secondary education and a generator of contributions to young people's life projects. Furthermore, by designing a methodology that involves constant interaction with the educational community, it facilitates the collection, analysis, and interpretation of information. Finally, career guidance is conceived as a comprehensive process in which multiple individual and social factors from all dimensions of the individual participate in order to make a responsible choice for oneself and for society.